REDISAIN SISTEM PEMBUMIAN DI HOTEL X JIMBARAN - Eland N.A, Khana; Janardana, I.G.N; Arta Wijaya, I.W (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i02.p1, 2021)
Due increases develop the electric power system, the more effective security system is needed. One of the security systems is the earthing system at Hotel X Jimbaran. After takes measurement the average measurement results of 1.14 ? ~ 2.47 ? at four different location points that cause the flow of overcurrent or overvoltage to electrical equipment. This study purpose to improve the existing earthing system to achieve earthing resistance <1? according to IEEE standards.This research method consist of several stages, first, survey location to measure the amount of soil resistance (R) to calculate the value of soil resistivity (?) then calculate the value of earthing resistance according to the type of earthing system to achieve an earthing resistance <1 ?, including the Vertical One Earthing Electrode System at Depth Z, Horizontal Earthing One Electrode System, Two Earthing Electrode System with S>L conditions, Two Earthing Electrode Earthing System with S<L conditions, Plate Earthing System and Grid-Rod Earthing System. The calculation analysis results design of the earthing system with earthing resistance <1? each fault location obtained different results. Building 1000 reccomended to choose plate earthing system in wet soil conditions with the result of earthing resistance 0,9594?; Building 2000 reccomended to choose grid rod earthing system in dry soil conditions with the result of earthing resistance 0,84?; Building 3000 reccomended to choose grid-rod earthing system in dry soil conditions with the result of earthing resistance 0,976?; and Ballroom reccomended to choose grid-rod earthing system in wet soil conditions with the result of earthing resistance 0,865?. Each location according to the analyzed earthing system recommendations, the most economical prices were calculated below IDR 10,000,000,- (Ten Million Indonesia Rupiah Currency), at Building 1000 with a total cost of IDR.4.034.000,-; Building 2000 with a total cost of IDR.6.698.650,-; Building 3000 with a total cost of IDR.7.448.200,-; and Ballroom with a total cost of IDR.7.352.200,-.